A Study on Perception of Employer Brand value in Chandigarh City - Ms. Pallavi Pahuja, Dr. Ranbir Singh (International Journal of Advanced Science and Technology, 2020)
Employer branding then is defined as a company’s ability to differentiate and promote this identity to a defined group of candidates that they’re interested in hiring. Branding has always been a core tool for marketers looking to win over the hearts and minds of consumers - the fact that it’s now a crucial part of the talent attraction formula shows us the influence that marketing is having on recruiting. The paper will provide an insight to demographics impacting employer brand. It will recommend the employer as to what strategies they can adopt to emerge as employer of choice in dynamic business environment.